(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Consensus of the people’s healthcare knowledge of ethno-medicinal plants in and around Lawachara national park was conducted from December 2014 to November 2015. The main aim of the study was to record and document plants species used for the treatment of various ailments and to find out level of consensus and agreement between informants regarding uses of plant for particular ailment categories. Data of medicinal uses of plants were recorded through semi-structured interviews, key informant discussions and informal conversations with local and ethnic people including herbal practitioners. A total of 124 medicinal plant species with 245 formularies to treat 53 ailments were recorded. For each species scientific name, local name, family, part used, ailments to be treated and mode of treatment are presented. Leaf is the dominant part used followed by fruit, root and rhizome, whole plant, seed, stem, bark, petiole, bulb, peduncle, latex and flower. In the documented 124 species, herbs were represented by 43%, trees by 31%, shrubs by 15% and climbers by 11% species. Oral consumption is the main mode of treatment in the study area and followed by external application. Maximum formularies were found in the six ailment groups including gastrointestinal complain, diarrhoea and dysentery, fever and cough, dermatitis, jaundice and impotence. According to the local people most of the plants (59%) were harvested from the park vegetation and minimum (41%) harvested from cultivated source. Maximum consensus values (Factor Informants Consensus (Fic) values more than 0.80) were obtained in case of cut and wounds and followed by Jaundice, Respiratory related ailments, Diabetes, Diarrhoea and dysentery, Anthelmintic, Gastrointestinal complain, Impotence, Dermatitis and High blood pressure. Chromolaena odoratum, Cericoides campanulata, Oroxylum indicum, Cuscuta reflexa, Averrhoa carambola, Cajanus cajan, Justicia adhatoda and Citrus aurantifolia showed 100% Fidelity values (Fl). Litsea glutinosa, Mikania cordata, Ocimum sanctum and Azadirachta indica were scored maximum Percent of Respondents knowledge values (PRK). It is recommended that species which showed high Fic, Fl and PRK values could be used for further ethno-lead phytochemical analysis to investigate active compounds to discover drugs from plants. Finally, a number of threats to medicinal plants were identified and some measures for conservation are also suggested. Asiat. Soc. Bangladesh, Sci. 43(1): 101-123, June 2017